Assessment of customers’ satisfaction from large buses services in urban public transportation: A case of Ubungo bus terminal - Bonaventura, Adam (Mzumbe University, 2024)
A dissertation submitted to School of Busines as a partial fulfillment of the requirement for the award of Master Degree of Business Administration in Corporate Management (MBA-CM) of Mzumbe University